EFFECT OF FUCOIDAN ON B16 MURINE MELANOMA CELL MELANIN FORMATION AND APOPTOSIS - Wang, Zhi-Jiang; Wei, Xu; Liang, Jian-Wen; Wang, Cai-Sheng; Kang, Yani (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background:Fucoidan is a complex sulfated polysaccharide extracted from brown seaweed and has a wide variety ofbiological activities. It not only inhibits cancer cell growth but also inhibits tyrosinase in vitro. Therefore, it is ofinterest to investigate the effect of fucoidan on B16 murine melanoma cells as the findings may provide new insightsinto the underlying mechanism regarding the inhibition of melanin formation by fucoidan. In the present study, weaimed to investigate the anti-melanogenic effect of fucoidan and its inhibitory effect on B16 cells.Materials and Methods: The influence of fucoidan on B16 melanoma cells and cellular tyrosinase was examined. Cellviability was examined by the cell counting kit-8 assay. Cellular tyrosinase activity and melanin content weredetermined using spectrophotometric methods and protein expression was analyzed by immunoblotting. Morphologicalchanges in B16 melanoma cells were examined by phase contrast microscopy and apoptosis was analyzed by flowcytometry.Results: In vitro studies were performed using cell viability analysis and showed that fucoidan significantly decreasedviable cell number in a dose-response manner with an IC50 of 550 ±4.3 μg/mL. Cell morphology was altered andsignificant apoptosis was induced when cells were exposed to 550 μg/mL fucoidan for 48 h.Conclusion: This study provides substantial evidence to show that fucoidan inhibits B16 melanoma cell proliferationand cellular tyrosinase activity. Fucoidan may be useful in the treatment of hyperpigmentation and as a skin-whiteningagent in the cosmetics industry.